Educational Implications of Early Menarche in a Socio-Cultural Context - Mukminah, Mukminah; Hirlan, Hirlan (Newinera Publisher, 2024)
This study aims to explore the psychosocial experiences and socio-cultural influences related to early menarche among elementary school girls (grades 4–6) in Central Lombok Regency. Employing a qualitative approach with a focused ethnographic-phenomenological design, the main participants were students who experienced early menarche, supported by key informants (mothers, teachers, peers, community leaders) selected through purposive and snowball sampling. Data were collected through in-depth interviews, observation, FGDs, and document analysis, and analysed thematically. Data credibility was ensured through triangulation, member checking, prolonged engagement, thick description, audit trails, and reflexivity. Findings indicate that early menarche can trigger confusion, fear, and potential trauma due to a mismatch between physical changes and emotional-cognitive readiness, compounded by lack of understanding. Negative associations with blood, pain, and perceived otherness intensify psychological distress. Girls may experience shame, anxiety, low self-esteem, and challenges in hygiene management. From a psychoanalytic lens, reactions include irrational fears and internalised stigma. Socially, early-maturing girls are vulnerable to isolation and bullying, exacerbated by peer misunderstanding and cultural taboos. Limited family support and silence around menstruation further heighten psychological burdens. The study highlights the need for comprehensive early puberty education for children, parents, and schools. Creating supportive, inclusive environments, destigmatising menstruation, and offering accessible psychological support are essential to help students adapt positively to pubertal changes.